The Role of Corporate Governance in Encouraging Improved Performance of Manufacturing Companies in the Capital Market - Wahyu Febri Ramadhan Sudirman; Saru Reza; Bunga Andhini; Muhamamd Riski (General Multidisciplinary Research Journal, 2025)
Introduction: This study aims to analyze the influence of corporate governance and financial structure on the financial performance and value of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Good corporate governance is believed to improve managerial efficiency and investor confidence, while an appropriate financial structure can support company stability and profitability. Methods: This study uses a quantitative approach with secondary data obtained from the financial statements of 45 manufacturing companies listed on the IDX from 2015-2019. Data analysis was conducted using multiple regression methods to determine the influence of each variable simultaneously and partially. Results: The results show that board diversity and the number of board directors have a positive and significant effect on all financial performance indicators and firm value. The board of commissioners has a positive effect on Tobin's Q but a negative effect on ROA and ROE. The audit committee does not significantly influence firm performance or value. Meanwhile, leverage is shown to have a negative effect on Tobin's Q and ROA, indicating that increasing debt can actually depress firm value and profitability. Conclusion and Suggestion: This study concludes that board diversity and effectiveness play a significant role in improving firm performance and value. Conversely, excessive use of debt can reduce a company's efficiency and competitiveness. Therefore, companies are advised to strengthen their governance structure by increasing board diversity and considering the debt ratio in their financial policies. Furthermore, future research is recommended to expand the sample to other sectors and add moderating variables such as institutional ownership to enrich the analysis of the relationship between governance and firm performance.